2016
DOI: 10.1186/s40709-016-0047-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-culturing bacteria and microalgae in organic carbon containing medium

Abstract: BackgroundMicroalgae frequently grow in natural environment and long-term laboratory cultures in association with bacteria. Bacteria benefit the oxygen and extracellular substances generated by microalgae, and reimburse microalgae with carbon dioxide, vitamins and so on. Such synergistic relationship has aided in establishing an efficient microalga-bacterium co-culturing mode. Obviously, the mutually beneficial relationship can be strengthened with the increase of the densities of microalgae and bacteria. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…Several studies have demonstrated that Muricauda bacteria are intimately associated with microalgae, including Symbiodiniaceae (19,31). However, their functional roles have yet be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that Muricauda bacteria are intimately associated with microalgae, including Symbiodiniaceae (19,31). However, their functional roles have yet be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher bacteria/algae ratio than optimum caused a lower assimilation of nutrients [18,26]. Bacteria in the activated sludge consume organic compounds and oxygen produced by the microalgae [27]. COD reduction below the effluent standard of sewage was obtained by controlling the proportion between the algae and bacteria.…”
Section: Prevention Of the Cod Re-increase By Sludge Inoculationmentioning
confidence: 99%
“…We identified three bacterial operational taxonomic units (OTUs), belonging to the Labrenzia and Marinobacter genera and an unclassified Chromatiaceae, which occurred in all strains of Symbiodiniaceae (Lawson et al, 2018). Members of the Marinobacter and Labrenzia commonly develop associations with microalgae (Han et al, 2016;Sandhya et al, 2017), and Marinobacter species have previously been isolated from other Symbiodiniaceae cultures (Frommlet et al, 2015). Notably, Labrenzia species (which comprised up to 38.4% of the Symbiodiniaceae microbiome; Lawson et al, 2018) can synthesize the DMS precursor, dimethylsulfoniopropionate (DMSP) (Curson et al, 2017), a sulfur compound also abundantly produced by Symbiodiniaceae (Broadbent et al, 2002;Deschaseaux et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%